Flow characteristics of fluid droplet obtained from air assisted atomizer - Pipatpong Watanawanyoo (2018)
Air assisted atomizer system was designed and developed for fuel injection. The present purpose is to utilize a low pressure in supplying of atomized fuel. Distilled water was used as test liquid on the experiments for the system of atomization. The results revealed air assisted atomizer had a capability to inject the test liquid in the range of the rates of 0.0019-0.00426 kg/s, with the use of air pressure supplied from 68.9 to 689 kPa. In this research, the test liquid supply pressure was kept constant and the air flow rate through the atomizer was varied over a range of air supply pressure to obtain the variation in air liquid mass flow ratio (ALR). The spray solidity was studied by taking pictures of the spray at different liquid air supply pressures. The experimental investigations suggest that spray cone angle tends to increase with increasing in air liquid mass flow ratio because the kinetic energy of the flow keeps on increasing. The solid cone spray has a pattern of penetration depth between 408-446 mm. and cone angle between 14.5-23.6°. It was observed that spray formed the solid cone at all the operating conditions. Copyright © 2011 by ASME.